806 Do you know when your inhaler is empty?. (17th August 2022) - Nagakumar, Prasad; Fullwood, Isobel; Evans, Teresa
Abstract : Aims: The presence of propellant in the metered dose inhalers (MDI) makes it challenging to identify when the inhaler is empty. Studies have shown that up to 86 actuations can be done just with the inhaler propellant after all the medication has been used up. 1 Salbutamol, the commonly used inhaler in the UK do not have the dose counter. The National Institute for Health and Care Excellence (NICE) recommends medication review at clinic appointments. 2 The Covid-19 pandemic has resulted in significant increase in remote consultations and monitoring brining out its own challenges in maintaining essential asthma care. We aimed to evaluate if patients identify when the inhaler is empty, clinical implications and the method of inhaler disposal. Methods: Design: Prospective, multicentre quality improvement project in hospitals who are part of the West mIdlands Paedaitric Severe Asthma Network (WMPSAN). Data collected from children with asthma and other respiratory conditions at hospital visits. Outcome measures: Children/carers attending hospital were asked how they identify an empty salbutamol inhaler, dose counters in the preventer inhalers and disposal practices were reviewed. Results: Data was collected from 157 children between October 2020 to September 2021. One hundred and seven (68.1%) were boys, the median age was 9.5 years (Interquartile Range IQR 2, 15). One hundred and eighteen children (75.2%) had asthma, 19 (12.1%) preschool wheeze, 5 (3.2%) cystic fibrosis and 15 (9.5%) bronchiectasis. In children with asthma or PSW (n=137), median asthma attacks requiring emergency department visits within the last 12 months were 2 (IQR, 0-10) and High Dependency Unit (HDU) admissions were 0.5 (IQR 0, 4). Eighty six (54.8%) said they were able to identify an empty inhaler correctly and seventy one (45.2%) were unsure/not aware. One hundred and five (69.9%) sought to identify medication left in the inhaler by shaking it and twenty seven (29.9%) looked for visible aerosol during actuation. Only three patients said that they will look at the dose counter and two actually kept count of actuations delivered. Inhaler technique was checked in 152/157 patients (96.8%) and was found to be satisfactory in 127/152 (83.5%). 138/157 brought a spacer device to the clinic and 127/138 (92%) were using an appropriate spacer for age. Neither the Salamol® or Ventolin® information leaflets contained any information on how to identify when 200 actuations had been performed. Symbicort® and Clenil® brands with dose counters had information on when to change the inhaler by looking at the number on the dose counter. Seretide® and Clenil® (without the dose counter) did not have any information regarding when to change the inhaler. Conclusion: Patients cannot reliably identify when their inhaler is empty. Along with focus on inhaler technique and use of spacer device, guidance should be provided on how to identify an empty inhaler as part of essential asthma care. There is urgent need for health regulators to work with the pharmaceutical industry to ensure that all inhalers are manufactured with dose counters and support recycling. References: Rubin: Chest:2002. NICE asthma quality standards:2018.